An Application Of Discriminant Analysis For The Evaluation Of Mineral Potential - C. F. Chung (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1977)
This paper will discuss an application of multivariate discriminant analysis to aid in predicting mineral potential from regional geological data and information on mineral deposits, with particular emphasis on the use of the logistic discriminant function. Logistic discriminant analysis is a generalization of standard discriminant analysis in that the discriminant analysis becomes applicable under a much wider class of distributions. As a practical example, the standard multiple discriminant analysis and the logistic discriminant analysis are applied to data from the Bathurst area in the Appalachian region of Canada and the results are compared with one another.